Dune : House Atreides - Herbert, Brian; Anderson, Kevin J., 1962-; Herbert, Frank (London : Hodder & Stoughton, 2000)
A prequel to "Dune," introducing the characters, alliances, treacheries, and hopes that form the foundation of the classic science-fiction saga.
Based on the Dune universe created by Frank Herbert.
Young Adult.
Young Adult
Keywords: Dune (Imaginary place) -- Fiction; Dune (Imaginary place) -- Fiction; Science fiction